Analisis terhadap Implementasi Hukum Dagang Internasional dalam Perdagangan Indonesia Studi Kasus pada Perjanjian Perdagangan Bebas Asean-China - Rama Yanti; Yusuf, Hudi (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
The ASEAN-China Free Trade Agreement (ACFTA) has posed significant challenges, benefits, and impacts on Indonesia's trade. In terms of challenges, the implementation of ACFTA has introduced several obstacles, including intensified competition with imported products from China, which could threaten certain domestic industry sectors. The use of qualitative methods is relevant because of its focus on gaining a deep understanding of the implementation of international trade law in Indonesia, using ACFTA as a case study. The objective of this research is to understand how the implementation of International Trade Law, particularly in the context of the ASEAN-China Free Trade Agreement (ACFTA), influences Indonesia's trade policies. The outcomes of this research are strategic steps needed to maximize the benefits of free trade with ASEAN and China while safeguarding domestic industry interests. Successful regional economic integration will bring significant economic benefits to all involved parties and strengthen economic cooperation in Southeast Asia.